Natural Polymer-Based Coatings for Animal-Derived Products: A Review of Applications, Functionality, Characterization, and Challenges - Márcio Vargas-Ramella; Noemí Echegaray; Paulo Cezar Bastianello Campagnol; José Manuel Lorenzo (Foods)
The global demand for sustainable packaging and animal-derived products’ perishability emphasizes the urgent need for biodegradable alternatives to petroleum-based materials (i.e., synthetic polymers or plastic). This narrative review explores the recent advancements in natural polymer-based coatings, comprising ingredients such as polysaccharides, proteins, and lipids, as well as their combination as multifunctional strategies for preserving meat, dairy, seafood, and eggs. These coatings act as physical barriers and can carry bioactive compounds, enhancing oxidative and microbial stability. Particular attention is placed on the structure-function relationships of biopolymers, their characterization through advanced techniques (e.g., Fourier Transform Infrared spectroscopy—FTIR, Scanning Electron Microscope—SEM, Differential Scanning Calorimetry—DSC, and Thermogravimetric analysis—TGA), and their functional properties (e.g., antimicrobial and antioxidant efficacy). Notably, food matrix compatibility is pivotal in determining coating performance, as interactions with surface moisture, pH, and lipids can modulate preservation outcomes. While several formulations have demonstrated promising results in shelf-life extension and sensory quality preservation, challenges remain regarding coating uniformity, regulatory compliance, and scalability. This narrative review highlights current limitations and future directions for the industrial application of these sustainable materials, aiming to link the gap between laboratory success and commercial feasibility.